2011
DOI: 10.1017/s0043887111000177
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Regime Type on Health: Does Redistribution Explain Everything?

Abstract: Many scholars claim that democracy improves population health. The prevailing explanation for this is that democratic regimes distribute health-promoting resources more widely than autocratic regimes. The central contention of this article is that democracies also have a significant pro-health effect regardless of public redistributive policies. After establishing the theoretical plausibility of the nondistributive effect, a panel of 153 countries for the years 1972 to 2000 is used to examine the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 79 publications
0
48
0
Order By: Relevance
“…Besley and Kudamatsu (2006) show this in a panel data model for the post-war period but without using country fixed effects. Wigley and Akkoyunlu-Wigley (2011) in a complementary study have shown that life expectancy is positively correlated with the history of democracy of a country. Kudamatsu 2012showed in the context of democratic transitions in Africa that health outcomes improved in countries which democratized compared to those that did not.…”
Section: Democracy and Health Outcomesmentioning
confidence: 95%
“…Besley and Kudamatsu (2006) show this in a panel data model for the post-war period but without using country fixed effects. Wigley and Akkoyunlu-Wigley (2011) in a complementary study have shown that life expectancy is positively correlated with the history of democracy of a country. Kudamatsu 2012showed in the context of democratic transitions in Africa that health outcomes improved in countries which democratized compared to those that did not.…”
Section: Democracy and Health Outcomesmentioning
confidence: 95%
“…There is also substantial empirical evidence that democracy distributes more to its citizens. The findings are robust across sev-eral different outcomes including welfare spending (Brown and Hunter 1999;Lake and Baum 2001;Rudra and Haggard 2005;Huber, Mustillo, and Stephens 2008), education (Brown and Hunter 2000;Stasavage 2005), and public health (Besley and Kudamatsu 2006;Akkoyunlu-Wigley 2011a and2011b). Przeworski et al (2000) treat the subject more expansively, presenting evidence that once democracies and dictatorships reach a developmental threshold, different patterns of production, consumption, and investment lead to superior welfare outcomes in democracies.…”
Section: Introductionmentioning
confidence: 98%
“…In the context of HIV, studies have shown how greater state capacity is positively associated with lower HIV infection rates , and how democratic conditions increase access to HIV prevention and treatment . Scholars have attributed these findings to how democratic political conditions enable active non‐governmental and citizen participation in healthcare, while according them greater civil liberties , which hold true as in the context of HIV organizational leadership . Nevertheless, several scholars find that regardless of regime type, contextual and historical precedence may impede or facilitate such responses to the epidemic .…”
Section: Introductionmentioning
confidence: 99%